Arrecifes coralinos de Bocas del Toro, Panamá: III. Distribución, estructura, diversidad y estado de conservación de los arrecifes de las islas Pastores, Cristóbal, Popa y Cayo Agua - Guzmán, Héctor M (1999)
Previous studies reported low coral diversity and poor reef development inside the marine protected area of Isla Bastimentos ( PNMIB), and it was recornmended to widen the survey further east into other areas of the archipelago of Bocas del Toro. This study describes reef distribution, structure and status in 24 reefs a10ng ca. 107 km of coastline in Pastores, Cristobal, Popa and Agua islands. We define for the first time the main center of diversity or "hot spot" zone for important sessile reef-building organisrns. Coral diversity increases to 57 species for the archipelago (89 % of Panama), adding up to 64 records for the country. There was a1so an increase to 29 and 53 species for octocorals and sponges, respectively. For local diversity, 96 %, 94 % .and 97 % of the total number of coral, octocoral and sponge species, respectively, are recorded inside the "hot spot." Based on our results, we recornmend the modification of the existing limil of the PNMIB to inelude reef areas with highest diversity and abundance of threatening species (e.g. Acrapara palmata, A. cervicarnis), or the creation of a network of marine protected areas within the archipelago